If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + -22 = 3(2p + -4) Reorder the terms: -22 + p = 3(2p + -4) Reorder the terms: -22 + p = 3(-4 + 2p) -22 + p = (-4 * 3 + 2p * 3) -22 + p = (-12 + 6p) Solving -22 + p = -12 + 6p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6p' to each side of the equation. -22 + p + -6p = -12 + 6p + -6p Combine like terms: p + -6p = -5p -22 + -5p = -12 + 6p + -6p Combine like terms: 6p + -6p = 0 -22 + -5p = -12 + 0 -22 + -5p = -12 Add '22' to each side of the equation. -22 + 22 + -5p = -12 + 22 Combine like terms: -22 + 22 = 0 0 + -5p = -12 + 22 -5p = -12 + 22 Combine like terms: -12 + 22 = 10 -5p = 10 Divide each side by '-5'. p = -2 Simplifying p = -2
| 6x-5=2x-11 | | -4+a=15 | | 6x+7y=13 | | 12x+5=8x+13 | | 2y-6=9-3y | | w^2+6w=-3 | | log(y)=1.6 | | 4=m+19 | | 9d-1=2d+20 | | x^3+6x+9=49 | | 2x^3+12x^2+22x+12=0 | | -5z+4+6z=40 | | 3x+5=2x+4 | | 47=(7z-3)-(4z-11) | | -6x-167=9x+88 | | 6u=96 | | -6x-167=88 | | 2x^2+8x+31=0 | | -x-2/7=x+1/6+4/7 | | 12x-18=10x+10 | | 5c-4b= | | 4n+1-5n=6n+7-9n | | 4b+8=7b-4 | | -6f=-36 | | 3x-1=5x+7 | | 15a-10=20a | | (2/5)+x=(-1/10) | | -6(18+3y)=-9 | | (2n+2)(2n-2)= | | 14x-(10x-3)=17 | | (2/5)+=(-1/10) | | 13+(-15x)=74-12 |